4-(Dimethylamino)pyridinium trichlorido[4-(dimethylamino)pyridine-κN]cobaltate(II) - Fatiha Guenifa; Nasreddine Hadjadj; Ouahida Zeghouan; Lamia Bendjeddou; Hocine Merazig (Acta Crystallographica Section E, 2013)
In the anion of the title compound, (C7H11N2)[CoCl3(C7H10N2)], the CoII ion is coordinated by one N atom from a 4-(dimethylamino)pyridine (DMAP) ligand and three Cl atoms, forming a CoNCl3 polyhedron with a distorted tetrahedral geometry. In the crystal, cations and anions are linked via weak N—H...Cl and C—H...Cl hydrogen bonds. Double layers of complex anions stack along the b- axis direction, which alternate with double layers of 4-(dimethylamino)-pyridinium cations.